2022
DOI: 10.1071/sh22060
|View full text |Cite
|
Sign up to set email alerts
|

Priorities in the implementation of partner services for HIV/STIs in high-income nations: a narrative review of evidence and recommendations

Abstract: Partner notification (PN) remains a crucial prevention tool to reduce sexually transmitted infection (STI) transmission and prevent STI-related morbidity. Although there have been a variety of different approaches taken to facilitate the notification, testing and management of sexual contacts of STIs and HIV, there is an increasing acknowledgement that these interventions are unscalable and have relatively little impact on disease transmission. At the same time, an expanding body of evidence supports a shift i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Disease intervention specialists often collect important surveillance data on STI cases that aid in the understanding of the current epidemiology of various STIs. 10 Sexually transmitted infection disease intervention also provides an opportunity to offer HIV services to those at increased risk including HIV field testing of STI contacts and linkage to HIV care for contacts with positive HIV tests. 11 Disease intervention specialists can also link contacts to HIV preexposure prophylaxis (PrEP) services.…”
Section: Disease Intervention Activitiesmentioning
confidence: 99%
“…Disease intervention specialists often collect important surveillance data on STI cases that aid in the understanding of the current epidemiology of various STIs. 10 Sexually transmitted infection disease intervention also provides an opportunity to offer HIV services to those at increased risk including HIV field testing of STI contacts and linkage to HIV care for contacts with positive HIV tests. 11 Disease intervention specialists can also link contacts to HIV preexposure prophylaxis (PrEP) services.…”
Section: Disease Intervention Activitiesmentioning
confidence: 99%
“…However, there is increasing recognition that our approach to CICT for HIV/STI is outmoded and in need of significant modernization. 20,21 The data supporting the efficacy of traditional CICT for HIV/STI in high-income nations is meager and of uncertain contemporary significance. Two randomized controlled trials conducted in the 1970 to 1980s among male STD clinic patients-only one of which was published-found that contact tracing undertaken by public health staff (ie, assisted partner notification services [APS]) was superior to leaving partner notification to patients themselves (ie, patient referral), [22][23][24] a finding also supported by a small randomized controlled trial performed in the late 1980s among patients with HIV.…”
Section: The Role Of Cict In Hiv and Stimentioning
confidence: 99%
“…For example, national guidance might establish broad standards, a health department would define local priorities and a plan for redeploying staff to confront major epidemics, and an HIV/STI program would establish a priority hierarchy of which cases to investigate that might place pregnant women with syphilis or unsuppressed HIV at the top. 20,21 Ordering priorities allows programs to adjust which cases are assigned depending on population-level morbidity and available staffing, though in some instances this flexibility is limited by mandates created by categorical funding. This is particularly important when DIS need to be reassigned to confront an emergency, as occurred with COVID-19, when HIV/STD and TB DIS were reassigned early in the epidemic and often became trainers for rapidly growing DIS teams.…”
Section: Defining Cict Prioritiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes education and awareness building, condom promotion, and the provision of vaccines (human papillomavirus and hepatitis A and B). Golden et al 11 argue for the need to modernise the partner notification (PN) system if we are to create meaningful change. The authors provide a valuable summary of the evidence for various approaches to PN in high-income countries, provide key principles for best practice and list priority research questions.…”
Section: Strengthening Current Servicesmentioning
confidence: 99%